Improving patient access to hepatitis C antiviral medicines in Switzerland: Understanding the financial risks for community pharmacies. Issue 3 (21st December 2018) - Berger, Jérôme; Bourdin, Aline; Pires, Fatima; Backes, Claudine; Perraudin, Clémence; Bugnon, Olivier
Abstract: Rationale: As observed in other countries, some patients may experiment difficulties in obtaining their hepatitis C antiviral medicines (HCVm) in Swiss community pharmacies. There is a lack of data related to access to HCVm at the patient level and notably related to the potential financial risks for the community pharmacies. Aims: (a) To evaluate the potential financial risks for community pharmacist associated with the delivery of HCVm in the Swiss healthcare system; (b) to explore the attitudes and experiences of community pharmacists related to these risks and their consequences for the patients. Method: A three‐step approach was chosen as follows: (a) estimation of costs, incomes, and gross financial results directly related to 3‐month treatment with Harvoni based on the drug delivery process (data from 68 patients over 2 years); (b) sensitivity analyses; (c) exploration of local community pharmacists' attitudes and experiences related to the delivery of HCVm in the canton of Vaud (Western Switzerland). Results: Two main risks were identified: (a) Incomes do not always cover costs; (b) reimbursement issues could lead to an increase in the requirement for working capital. According to the survey, 23% (14/60) of pharmacies refused to deliver HCVm to at least one patient, and these patients had to find a solution mostly on their own. Conclusions: The scenario analysis clarifies the causes of the possible refusal to deliver HCVm. With the growing number of high‐priced medicines, the healthcare systems should have a clear strategy to encourage their delivery by community pharmacies by ensuring seamless and collaborative care for patients. The community pharmacists could be accountable to provide such services—if they get the education, training, and remuneration.